Inorganic Carbon and pCO2 Variability During Ice Formation in the Beaufort Gyre of the Canada Basin. Issue 6 (21st June 2019) - DeGrandpre, Michael D.; Lai, Chun‐Ze; Timmermans, Mary‐Louise; Krishfield, Richard A.; Proshutinsky, Andrey; Torres, Daniel
Abstract: Solute exclusion during sea ice formation is a potentially important contributor to the Arctic Ocean inorganic carbon cycle that could increase as ice cover diminishes. When ice forms, solutes are excluded from the ice matrix, creating a brine that includes dissolved inorganic carbon (DIC) and total alkalinity ( A T ). The brine sinks, potentially exporting DIC and A T to deeper water. This phenomenon has rarely been observed, however. In this manuscript, we examine a ~1 year p CO2 mooring time series where a ~35‐μatm increase in p CO2 was observed in the mixed layer during the ice formation period, corresponding to a simultaneous increase in salinity from 27.2 to 28.5. Using salinity and ice based mass balances, we show that most of the observed increases can be attributed to solute exclusion during ice formation. The resulting p CO2 is sensitive to the ratio of A T and DIC retained in the ice and the mixed layer depth, which controls dilution of the ice‐derived A T and DIC. In the Canada Basin, of the ~92 μmol/kg increase in DIC, 17 μmol/kg was taken up by biological production and the remainder was trapped between the halocline and the summer stratified surface layer. Although not observed before the mooring was recovered, this inorganic carbon was likely later entrained with surface water, increasing the p CO2 at the surface. It is probable that inorganic carbon exclusion during ice formation will have an increasingly important influence on DIC and p CO2 in the surface of the Arctic Ocean as seasonal ice production and wind‐driven mixing increase with diminishing ice cover. Plain Language Summary: When sea ice forms, the dissolved solutes are squeezed out of the ice matrix, forming a dense brine that can sink into deeper water. This process has a potentially important role in the inorganic carbon cycle because dissolved inorganic carbon can sink with the brine, exporting it from the surface ocean and increasing the sea surface CO2 partial pressure ( p CO2 ). We deployed a p CO2 sensor at 30‐m depth in the Canada Basin, the largest of the Arctic Ocean subbasins, that documented an increase in p CO2 during the fall to winter ice formation period. This increase correlated with an increase in salinity over the same time period. A simple model calculation supports that the increase in p CO2 and inorganic carbon is primarily due to ice formation. This finding has important implications for the future inorganic carbon cycle as seasonal ice formation increases due to loss of perennial ice cover in the Arctic. Key Points: We deployed a p CO2 sensor in the northwest Canada Basin of the Arctic Ocean; the time series shows a steady increase from fall to winter The p CO2 increase is attributed to sea ice formation that excludes inorganic carbon; the inorganic carbon concentrated in the mixed layer Ice exclusion of inorganic carbon could become an increasingly important part of the Arctic Ocean carbon cycle with diminishing ice cover